Implementation of Raw Material Control in Order to Achieve Production Target at PT. Budi Starch N Sweetener - Imaduddin, Imaduddin; Dasilpa, Sispa; Malasari, Nur; Sari, Reski Nurlia; Prayoga, Putri Regina (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
This study aims to describe the Implementation of Raw Material Control in the Framework of Achieving Production Targets at PT. Budi Starch N Sweetener. The type of research used is descriptive qualitative, which is a study intended to collect data and information about a problem and facts about the object and at the research location according to what it is at the time the research takes place. This research was conducted in Likuloe Hamlet, Bontoramba Village, Palangga District, Gowa Regency by selecting 2 (two) sources who were considered representative representing their group consisting of 1 (one) tapioca flour business owner and 1 (one) Head of Production Section. The data collection technique used in this study used in-depth interview techniques, observation, and documentation techniques. The results of the study showed that the tapioca flour business in Likuloe Hamlet, Bontoramba Village, Palangga District, Gowa Regency had carried out good raw material control to achieve production targets.